Safety of TeaCrine®, a non-habituating, naturally-occurring purine alkaloid over eight weeks of continuous use - Taylor, Lem (J Int Soc Sports Nutr, 2016)
BACKGROUND: Theacrine (1,3,7,9-tetramethyluric acid) is a purine alkaloid found in certain coffee (Coffea) species, fruits (Cupuacu [Theobroma grandiflorum]), and tea (Camellia assamica, var. kucha) that has anti-inflammatory, analgesic, and neuro-locomotor properties. Recent preliminary research has also reported increased feelings of energy, reduced fatigue, and strong effects on improving focus, concentration, and motivation to exercise. The purpose of this study was to examine the safety and non-habituating effects of TeaCrine®, a nature-identical, chemically equivalent bioactive version of theacrine. METHODS: Sixty healthy men (mean ± SD age, height, weight: 22.9 ± 4.7 years, 183.5 ± 9.2 cm, 86.5 ± 13.7 kg) and women (22.3 ± 4.5 years, 165.2 ± 12.3 cm, 69.0 ± 17.4 kg) were placed into one of three groups: placebo (PLA, n = 20), 200 mg TeaCrine® (LD, n = 19) or 300 mg Teacrine® (HD, n = 21) and ingested their respective supplement once daily for 8 weeks. Primary outcomes were fasting clinical safety markers (heart rate, blood pressure, lipid profiles, hematologic blood counts, biomarkers of liver/kidney/immune function) and energy, focus, concentration, anxiety, motivation to exercise, and POMS measured prior to daily dosing to ascertain potential tachyphylactic responses and habituation effects. Data were analyzed via two-way (group × time) ANOVAs and statistical significance was accepted at p < 0.05. RESULTS: All values for clinical safety markers fell within normal limits and no group × time interactions were noted. No evidence of habituation was noted as baseline values for energy, focus, concentration, anxiety, motivation to exercise, and POMS remained stable in all groups across the 8-week study protocol. CONCLUSIONS: These findings support the clinical safety and non-habituating neuro-energetic effects of TeaCrine® supplementation over 8 weeks of daily use (up to 300 mg/day). Moreover, there was no evidence of a tachyphylactic response that is typical of neuroactive agents such as caffeine and other stimulants.